Pedagogical models for tambaqui creation (Colossoma macropomum) in diverse environments (Research, Society and Development, 2021)
The project "Technology transfer through training and technical assistance for tambaqui breeders (Colossoma macropomum) in the Marajó/PA archipelago is characterized by the opportunity for training, dissemination of technologies, quality academic professional training to students and others involved. For this, the municipality of Curralinho was the stage of extensionist actions realized by Instituto Federal de Educação, Ciência e Tecnologia do Pará (IFPA), Campus Breves. Active methodologies were used through the participation of teachers, fish farmers and students in the construction of pedagogical models. Thus, the objective of this work was to evaluate the use of different models for tambaqui creation. Three models were produced with perspective of implantation in different environments for the region of Marajó: floodplain area, dry land area and field area. A total of 13 fish farmers participated in this action, with whom the power of fixation attention, the understanding, the reflection and the sufficiency of time for each type of model built was evaluated. The Likert scale was used to analyze the data. The results showed that fish farming in floodplain areas presented the highest rates in the parameters studied, while the dry land area and field area models were less interesting in the opinions of the participants. In conclusion, the use of active methodologies through models improved the learning process of the fish farmers during the educational actions of the extension project in aquaculture.